Middle East - Ham, Anthony; Barbarani, Sofia; Lee, Jessica; Maxwell, Virginia; Robinson, Daniel; Sattin, Anthony; Symington, Andy; Walker, jenny (Lonely Planet guidebooks., 2015)
Lonely Planet Middle East is your passport to the most relevant, up-to-date advice on what to see and skip, and what hidden discoveries await you. Be awed by the grandeur of Istanbul's Aya Sofia, contemplate history at Jerusalem's Dome of the Rock, and explore the wonder of Giza's Pyramids; all with your trusted travel companion.